Analisis Kualitas Sistem Informasi Absensi Karyawan di SMP Negeri 15 Jakarta dengan Metode Mccall - Anang Maulana; Ahmad Taufik (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
The Employee Attendance Information System is a crucial component in human resource management at SMP Negeri 15 Jakarta, a vocational high school institution. This study aims to analyze the quality of the attendance information system using the McCall Method, which provides a comprehensive evaluation framework. The analysis measures indicators of correctness, usability, reliability, and efficiency. The evaluation results show that the attendance system achieved average scores ranging from 0.74 to 0.76, with a total score of 298 out of an ideal score of 140, placing it in the good category. While the system functions well and positively contributes to management, there remains significant room for further development. This study identifies factors influencing system quality, which can serve as a basis for future improvements. The recommendations derived are expected to support the development of a more effective and efficient attendance information system, enhancing employee discipline and productivity, and contributing to improved educational quality for students.